ЗУЛЬФИЯ - МУҚАДДЕС ЎАТАН ТУЙҒЫСЫ ЖЫРШЫСЫ … - Алламбергенов, К. (SCIENCE and SOCIETY, 2021)
The article determines the place of Zulfiya Israilova, who is proud of the nation and lived in the end of the XXth century and the beginning of the XXI century, in the Uzbek and World literature. Furthermore, there is presented detailed analysis of her poem on themes: Motherland, spirit of the time, fade of the nation, and love to the birthplace. Author attributes affect of Zulfiya Israilova on Karakalpka poet, especially on poetess. Generally, author discusses relationship of Zulfiya with Karakalpak Literature.
Keywords: Zulfiya’s poetry; special features; Zulfiya and Eastern poetry; Delhi; Africa-Asia writers’ conference; Motherland; birthplace; spirit of the time; Zulfiya and Karakalpak Literature